Prehospital Care and Clinical Characteristics of Patients With Diabetic Emergencies at A Tertiary Care Hospital in Mysuru, India: An Observational Study with Emphasis on Geospatial Analysis - Priyanga Thirunavukkarasu; Madhu Basavegowda; Mounika Sree Manivasagan; Chaithra Mallaiah; Aravindhan Ranganathan; Sulochanadevi B Chakrashali (Medsci Publications, 2024)
Background: Diabetes Mellitus is a chronic, progressive disease with serious complications, and its prevalence is rising, especially in India. This study evaluates the clinical characteristics, prehospital care, and proximity to healthcare facilities among patients presenting with diabetic emergencies at a tertiary care hospital. Methodology: A cross-sectional study was conducted with 70 diabetic emergency patients (hyperglycemia, hypoglycemia, and DKA). Data were collected using a semi-structured questionnaire assessing clinical characteristics, prehospital care, and health-seeking behavior. Geospatial analysis measured the distance from patients' residences to the hospital. Results: Among the 70 participants, 36 (51.4%) were over 60 years old, and 55 (78.6%) were male. The most common symptoms were polyuria (85.7%) and excessive thirst (57.1%). Hyperglycemia was diagnosed in 68 (97.1%) cases, with 46 (65.7%) showing high random blood sugar levels (>200 mg/dl). Severe symptoms led 55 (78.6%) to seek emergency care, with 17 (24.3%) requiring ambulance services. Geospatial analysis revealed that 50% of patients lived 1-50 km from the hospital. Conclusion: The study emphasizes the need for improved access to diabetes care near patients' homes to prevent emergencies, highlighting the importance of decentralizing services to improve health outcomes.